PENGARUH RASIO KEUANGAN TERHADAP PERTUMBUHAN LABA PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - IMA INDRIYANI (Program Studi Magister Manajemen FE Unsri, 2015)
This study aims to examine the Financial Ratio Effect on Growth Profit On Mining Companies Listed on the Indonesia Stock Exchange (IDX). The sample selection using purposive sampling of 17 companies listed company only 9 samples taken. The independent variables studied were the financial ratio that consists of the Current Ratio (CR), debt to asset ratio (DAR), the total asset turnover (TATO) and return on assets (ROA), while the dependent variable is the growth in earnings (PL). The results of this study showed that simultaneous Currents Ratio, Debt To Asset Ratio, Total Asset Turnover and Return On Asset significantly affect earnings growth in the mining company listed on the Stock Exchange. Partially, only the variable return on assets which have a significant effect on earnings growth. While Currents variable Ratio, Debt To Asset Ratio, Total Asset Turnover no significant effect on earnings growth in mining companies listed on the Stock Exchange.